Multi-standard reconfigurable wireless transmitter architectures - Pires, Sérgio Carlos da Conceição (2014)
The continuous demand for highly efficient wireless transmitter systems has triggered an increased interest in switching mode techniques to handle the required power amplification. The RF carrier amplitude-burst transmitter, i.e. a wireless transmitter chain where a phase-modulated carrier is modulated in amplitude in an on-off mode, according to some prescribed envelope-to-time conversion, such as pulse-width or sigma-delta modulation, constitutes a promising architecture capable of efficiently transmitting signals of highly demanding complex modulation schemes. However, the tested practical implementations present results that are way behind the theoretically advanced promises (perfect linearity and efficiency). My original contribution to knowledge presented in this thesis is the first thorough study and model of the power efficiency and linearity characteristics that can be actually achieved with this architecture. The analysis starts with a brief revision of the theoretical idealized behavior of these switched-mode amplifier systems, followed by the study of the many sources of impairments that appear when the real system is implemented. In particular, a special attention is paid to the dynamic load modulation caused by the often ignored interaction between the narrowband signal reconstruction filter and the usual single-ended switched-mode power amplifier, which, among many other performance impairments, forces a two transistor implementation. The performance of this architecture is clearly explained based on the presented theory, which is supported by simulations and corresponding measured results of a fully working implementation. The drawn conclusions allow the development of a set of design rules for future improvements, one of which is proposed and verified in this thesis. It suggests a significant modification to this traditional architecture, where now the phase modulated carrier is always on – and thus allowing a single transistor implementation – and the amplitude is impressed into the carrier phase according to a bi-phase code.